Analisis Pengaruh Lean Manufacturing dan Personal Protective Equipment Terhadap Kinerja Karyawan Melalui Mediasi 5S dengan Pendekatan SMARTPLS (Studi Kasus: Departemen Operasional Produksi, Quality, PPIC di PT. XYZ) - Pauji, Ahmad; Iskandar, Hendi; Tarman, Tarman (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of Lean Manufacturing and Personal Protective Equipment (PPE) on employee performance through the mediation of 5S in the Operations Department of PT. XYZ. The method used is quantitative with a SEM-PLS approach using the SmartPLS 4 application. Data was collected from 217 respondents. The results indicate that Lean and PPE do not have a significant direct effect on employee performance. However, both have a significant effect on the implementation of 5S. Lean has a t-statistic of 8.023 and PPE has a t-statistic of 10.116, both of which are > t-table 1.64 and p-value < 0.05. The implementation of 5S also significantly influences employee performance (t-statistic = 11.122). Additionally, 5S significantly mediates the relationship between Lean and PPE and employee performance, with t-statistics of 6.518 and 7.365, respectively. These findings indicate that 5S plays a crucial role in linking work systems and safety to employee performance.